The Protecting Effect of Deoxyschisandrin and Schisandrin B on HaCaT Cells against UVB-Induced Damage - Hou, Wei; Gao, Wei; Wang, Datao; Liu, Qingxiu; Zheng, Siwen; Wang, Yingping (PLOS ONE, 2015)
Schisandra chinensis is a traditional Chinese medicine that has multiple biological activities, including antioxidant, anticancer, tonic, and anti-aging effects. Deoxyschisandrin (SA) and schisandrin B (SB), the two major lignans isolated from S. chinensis, exert high antioxidant activities in vitro and in vivo by scavenging free radicals, such as reactive oxygen species (ROS). Ultraviolet B-ray (UVB) radiation induces the production of ROS and DNA damage, which eventually leads to cell death by apoptosis. However, it is unknown whether SA or SB protects cells against UVB-induced cellular DNA damage. Our study showed that both SA and SB effectively protected HaCaT cells from UVB-induced cell death by antagonizing UVB-mediated production of ROS and induction of DNA damage. Our results showed that both SA and SB significantly prevented UVB-induced loss of cell viability using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays. Dichloro-dihydro-fluorescein diacetate (DCFH-DA) assays showed that the production of ROS following UVB exposure was inhibited by treatment with SA and SB. Moreover, SA and SB decreased the UVB-induced DNA damage in HaCaT cells by comet assays. In addition, SA and SB also prevented UVB-induced cell apoptosis and the cleavage of caspase-3, caspase-8 and caspase-9. In a word, our results imply that the antioxidants SA and SB could protect cells from UVB-induced cell damage via scavenging ROS.